Different levels of implicit emotional recognition in posterior cortical atrophy (PCA) - González Gadea, María Luz (2014)
Previous single-case reports in Posterior Cortical Atrophy (PCA) have shown preserved non-conscious visual recognition despite the absence of explicit recognition. In this study we investigated three levels of visual recognition in both a female patient with PCA and a control group during the presentation of neutral, positive, and negative affective stimuli. Our results confirmed the profile of impaired explicit recognition and intact psychophysiological responses in the patient. In addition, she was able to implicitly recognize the valence and intensity of arousal of these stimuli. We suggest that implicit emotional awareness may mediates explicit and psychophysiological recognition in PCA.